A Case-Control Study between Gene Polymorphisms of Polyunsaturated Fatty Acid Metabolic Rate-Limiting Enzymes and Acute Coronary Syndrome in Chinese Han Population. (28th February 2013) - Song, Zikai; Cao, Hongyan; Qin, Ling; Jiang, Yanfang
Abstract : The purpose of this study is to analyze the relationship between the polymorphisms of fatty acid desaturase 1 ( FADS 1), fatty acid desaturase 2 ( FADS 2), and elongation of very long-chain fatty acids-like 2 ( ELOVL 2) and acute coronary syndrome (ACS) in Chinese Han population. Therefore, we selected three single nucleotide polymorphisms (SNPs) from these candidate genes and genotyped them using PCR-based restriction fragment length polymorphism analysis in 249 ACS patients and 240 non-ACS subjects, as were Han Chinese ancestry. The results showed that rs174556 in the FADS 1 gene is found to be in allelic association (P = 0.003 ) and genotypic association (P = 0.036 ) with ACS. The frequencies of rs174556 minor allele (T) in case group were obviously higher than in control group. The trans-phase gene-gene interaction analysis showed that the combined genotype of rs174556 (T/T) and rs3756963 (T/T) was associated with ACS (P = 0.031 ). And the results suggest that, for rs174556 C>T, the CT/TT genotypes were more likely to lead in ACS in subjects with hypertension after correction of all risk factors (O R = 4.236, 95% CI, 2.216–7.126). These findings suggest that the polymorphisms of rs174556 in the FADS 1 gene are very likely to be associated with ACS in Chinese Han population, especially in subjects with hypertension.